Discovery of potential pharmacodynamic ingredients of Dang-Gui-Si-Ni decoction based on absorbed ingredients and molecular docking. (15th July 2021) - Li, Yun; Liu, Shan-Shan; Guo, Zhong-Yuan; Yi, Hong; Li, Chun; Chen, Liang-Mian; Gao, Hui-Min; Yan, Li-Hua; Zhang, Wen-Wen; Feng, Xia-Xia; Zhao, Jing-Yuan; Liu, Xiao-Qian; et al.
Abstract: Ethnopharmacological relevance: The Dang-Gui-Si-Ni (DGSN) decoction as a classic prescription has been widely used for thousands of years in the clinical practice of traditional Chinese medicine (TCM). Especially in recent years, the potential efficacy of TCM for the treatment of Raynaud's syndrome has attracted great attention as there are still no specific remedies for this disease. However, the active constituents and underlying mechanisms responsible for the therapeutic benefits are not well understood, which makes it difficult to ensure quality control or to design research and drug development strategies. To identify the potential pharmacodynamic ingredients (PPIs) of TCM will help to achieve suitable process control procedures for industrial production and large-scale manufacturing. Aim of the study: In the present study, we propose a multi-dimensional qualitative analysis method combining water-decoction spectra, in-vitro intestinal absorption spectra, in-vivo plasma spectra, and molecular docking of components to quickly identify the PPIs for the DGSN decoction of TCM. Materials and methods: Water-based decoctions of DGSN were prepared in accordance with the clinical use registered in ancient books. Ultra-high-performance liquid chromatography-quadrupole-time of flight mass spectrometry (UHPLC-Q/TOF-MS) coupled with computerized modelling activity screening was used to quickly identify the PPIs of the DGSN decoction. Bioactive compounds absorbed in vitro were identified using the everted intestinal sac model from rats and compounds absorbed in vivo were confirmed in portal vein blood samples obtained following oral administration in rats. Molecular docking validation experiments were adopted to predict the binding activity to coagulation factors I, II, VII, X, and IX. The active components were further confirmed by pharmacodynamics analysis. The anticoagulant activity of the DGSN decoction was verified using rat models. Results: Thirty-one compounds were identified in the DGSN decoction. According to the in vivo experiments, 22 compounds that could be absorbed in vivo were detected by the everted intestinal sac model in rats. This model greatly reduces the scope of PPIs and is easy to perform. Ten compounds were detected in the portal vein blood in rats. The compounds detected in plasma provide stronger evidence supporting the PPIs. Molecular docking in vitro experiments indicated that 7 compounds exhibited better binding activity with coagulation factors I, II, VII, X, and IX. The animal experiments confirmed that the DGSN decoction could improve the microcirculation, providing indirect proof of anticoagulant activity suggested by the molecular docking studies. Finally, based on the multi-dimensional methods, 9 potential compounds present in the DGSN decoction were identified as PPIs (i.e., ferulic acid, paeoniflorin, albiflorin, chlorogenic acid, cryptochlorogenic acid, liquiritin, liquiritin apioside, cinnamaldehyde and glycyrrhizic acid). Conclusion: Overall, this study combined the water-decoction spectra, intestinal absorption spectra in vitro, plasma spectra in vivo, and molecular docking studies to establish a multi-dimensional qualitative analysis method of the DGSN decoction. Meanwhile, 9 compounds in DGSN decoction were identified as PPIs using this method, and are proposed for application as quality standards for complex TCM prescriptions. Graphical abstract: Image 1